The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/smll.201803529
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocarrier Generation with Selectable Wavelengths by M‐Decorated‐CuInS2 Nanocrystals (M = Au and Pt) Synthesized in a Single Surfactant Process on MoS2 Bilayers

Abstract: has attracted much attention and been extensively studied as the transistor [7] or photodetector devices. [8,9] However, the absorption of the incident light may be limited from the reduced atomic thickness of the MoS 2 . Meanwhile, plasmonic materials, especially the noble metals (e.g., platinum and gold), have been reported to facilitate the strong light-matter interaction and carrier transportation at the intimate interface of semiconductor-metal nanodomains. [10,11] Previous works have revealed the enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…At the light intensity of 8mWcm À2 and ab ias of 10 V, the R and detectivity of HFA photodetector were calculated as 0.95 mAW À1 (Figure 4d)a nd 3 10 11 Jones (Figure S6), respectively.C ompared to the results of photodetectorso fi norganic 2D materials, the responsivity of device is smaller than that of WS 2 ,A u-CIS/MoS or Pt-CIS/MoS. [41][42][43] However,d etectivity of HFA photodetector exhibits excellent result. (TableS5) It is expectedt od ecrease the electrode distance to improve the photoresponsivity.…”
Section: Resultsmentioning
confidence: 87%
“…At the light intensity of 8mWcm À2 and ab ias of 10 V, the R and detectivity of HFA photodetector were calculated as 0.95 mAW À1 (Figure 4d)a nd 3 10 11 Jones (Figure S6), respectively.C ompared to the results of photodetectorso fi norganic 2D materials, the responsivity of device is smaller than that of WS 2 ,A u-CIS/MoS or Pt-CIS/MoS. [41][42][43] However,d etectivity of HFA photodetector exhibits excellent result. (TableS5) It is expectedt od ecrease the electrode distance to improve the photoresponsivity.…”
Section: Resultsmentioning
confidence: 87%
“…This is very similar to the ITIC theory. For ions, it is very small substance moving to form the current [17][18][19][20]. In addition, many nanomaterials and devices used this theory to explain their model [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that in the efficient photon management, QD converter can be widely used in solar cells [17,18], LEDs [19,20], and photodetectors [21][22][23]. Especially, QD photodetectors with selectable wavelengths and high responsivity and on/off ratio have been reported [24,25]. Recently, QDs were also applied for water splitting due to its superior electrocatalytic and photocatalytic properties [26].…”
Section: Introductionmentioning
confidence: 99%